Mosquito Diversity and Population Genetic Structure of Six Mosquito Species From Hainan Island - Li, Siping; Jiang, Feng; Lu, Hong; Kang, Xun; Wang, Yanhong; Zou, Zhen; Wen, Dan; Zheng, Aihua; Liu, Chunxiang; Liu, Qiyong; Kang, Le; Xia, Qianfeng; et al. (Frontiers in Genetics, 2020)
Hainan is a tropical island in southern China with abundant mosquito species, putting Hainan at risk of mosquito-borne virus disease outbreaks. The population genetic diversity of most mosquito species on Hainan Island remains elusive. In this study, we report the diversity of mosquito species and the genetic diversity of the predominant species on Hainan. Field populations of adults or larvae were collected from 12 regions of Hainan Island in 2018 and 2019. A fragment of the mitochondrial cytochrome c oxidase subunit I (coxI) gene was sequenced from 1228 mosquito samples and used for species identification and genetic diversity analysis. Twenty-three known mosquito species from the genera Aedes, Armigeres, Culex, Mansonia, and Anopheles and nine unconfirmed mosquito species were identified. Aedes albopictus, Armigeres subalbatus, and Culex pipiens quinquefasciatus were the most prevalent mosquito species on Hainan. The regions north of Danzhou, Tunchang, and Qionghai exhibited high mosquito diversity (26 species). The order of the total haplotype diversity and nucleotide diversity of the populations from high to low was as follows: Culex tritaeniorhynchus, Ar. subalbatus, Culex pallidothorax, Culex gelidus, Ae. albopictus, and Cx. pipiens quinquefasciatus. Tajima’s D and Fu’s Fs tests showed that Ae. albopictus, Cx. pipiens quinquefasciatus, Cx. tritaeniorhynchus, and Cx. gelidus had experienced population expansion, while the Ar. subalbatus and Cx. pallidothorax populations were in genetic equilibrium. Significant genetic differentiation existed in the overall populations of Ae. albopictus, Ar. subalbatus, Cx. pipiens quinquefasciatus, and Cx. pallidothorax. The Ae. albopictus populations on Hainan were characterized by frequent gene exchange with populations from Guangdong and four other tropical countries, raising the risk of viral disease outbreaks in these regions. Two subgroups were reported in the Ar. subalbatus populations for the first time. Our findings may have important implications for vector control on Hainan Island.